2021
DOI: 10.1038/s41419-021-04407-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased PRC2 activity supports the survival of basal-like breast cancer cells to cytotoxic treatments

Abstract: Breast cancer (BC) is the most common cancer occurring in women but also rarely develops in men. Recent advances in early diagnosis and development of targeted therapies have greatly improved the survival rate of BC patients. However, the basal-like BC subtype (BLBC), largely overlapping with the triple-negative BC subtype (TNBC), lacks such drug targets and conventional cytotoxic chemotherapies often remain the only treatment option. Thus, the development of resistance to cytotoxic therapies has fatal consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…In a recent study, we leveraged the WAP-T mammary carcinoma mouse model system (parental G-2 cells; pG-2) to study the mechanisms underlying resistance to combined cytotoxic chemotherapy (cyclophosphamide, adriamycin, 5-fluorouracil; short CAF) and confirmed the enrichment of EMT-associated features along with the disease progression (Fig. 1 A), [ 17 , 18 ]. Hence, we sought to validate the activation of the EMT transcriptional program in a human BLBC cell line (HCC1806) upon different conventional chemotherapy treatments (CAF, cisplatin and paclitaxel).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…In a recent study, we leveraged the WAP-T mammary carcinoma mouse model system (parental G-2 cells; pG-2) to study the mechanisms underlying resistance to combined cytotoxic chemotherapy (cyclophosphamide, adriamycin, 5-fluorouracil; short CAF) and confirmed the enrichment of EMT-associated features along with the disease progression (Fig. 1 A), [ 17 , 18 ]. Hence, we sought to validate the activation of the EMT transcriptional program in a human BLBC cell line (HCC1806) upon different conventional chemotherapy treatments (CAF, cisplatin and paclitaxel).…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies of our group and others identified that epigenetic mechanisms are frequently involved in the EMT transcriptomic program induction of cancer cells [ 18 22 ]. To better understand factors that could be responsible for the transcriptional changes observed in BLBC cells upon chemotherapy treatment and to identify potentially druggable upregulated epigenetic effectors, we re-analyzed the mRNA-seq data of our previous study [ 18 ]. We identified 76 differentially regulated epigenetic factors (log2FC ≥ l0.7l, p -adj < 0.05), of which only 9 were significantly upregulated (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we treated WAP-T tumors with a combination of Cyclophosphamide/Adriamycin/5-fluorouracil (short CAF) and observed that a single cycle of this treatment is not able to eradicate the disease [ 16 ]. Notably, recurrences recapitulated the human situation, showing increased aggressiveness and dissemination properties, pronounced epithelial-to-mesenchymal transition (EMT), and cancer stem cell (CSC) traits [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%